PENGARUH FINANCIAL TECHNOLOGY DAN LITERASI KEUANGAN TERHADAP KEPATUHAN PENYUSUNAN PELAPORAN KEUANGAN UMKM DI PRIANGAN TIMUR - Mohamad Fazar Fadilah; Intan Rahayu; Aulia Anastasyia Syakila; Renti Senteri; Naldy Muhammad Ramdhan; Muhammad Dava Nugraha (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This research focuses on the influence of Financial Technology (FinTech) and financial literacy on compliance with the preparation of MSME financial statements in East Priangan. The urgency lies in filling the gap in the literature, as most previous studies have highlighted FinTech in the context of inclusion and financial literacy in investment decisions, but have not integrated the two in the compliance aspect of MSME financial reporting, especially at the regional level. In terms of policy, the results of the research can be a reference for the government in designing financial literacy programs and encouraging effective FinTech adoption. The practical impact is that MSMEs are expected to be able to strengthen governance, increase access to financing, and competitiveness. The purpose of this study is to test the influence of FinTech and financial literacy, both partially and simultaneously, on compliance with the preparation of financial statements. The method used is explanatory quantitative with a survey of MSMEs using FinTech for at least one year, analyzed through multiple regression and equipped with interview triangulation